2008
DOI: 10.1186/1471-2172-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase activity in the hematopoietic tissue of a crustacean, Pacifastacus leniusculus, importance in hemocyte homeostasis

Abstract: Background: Transglutaminases (TGases) form a group of enzymes that have many different substrates and among the most well known are fibrin for Factor XIIIa and the clotting protein in crustaceans. We also found that TGase is an abundant protein in the hematopoietic tissue (Hpt) cells of crayfish and hence we have studied the possible function of this enzyme in hematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 30 publications
(36 reference statements)
4
95
0
Order By: Relevance
“…TGase activity is important for stabilizing the matrix, and ECM loosening is achieved through a decrease in extracellular transglutaminase activity (Lin et al, 2008a). When TGase activity was silenced in HPT tissue culture, cells migrated out of the tissue (Lin et al, 2008a).…”
Section: Molecular Regulation Of Hemocyte Synthesis Differentiation mentioning
confidence: 99%
See 1 more Smart Citation
“…TGase activity is important for stabilizing the matrix, and ECM loosening is achieved through a decrease in extracellular transglutaminase activity (Lin et al, 2008a). When TGase activity was silenced in HPT tissue culture, cells migrated out of the tissue (Lin et al, 2008a).…”
Section: Molecular Regulation Of Hemocyte Synthesis Differentiation mentioning
confidence: 99%
“…In comparison, the Pacifastacus transcriptome expressed several GATA factors, one of which was specifically similar to Srp. Previous studies have shown that GATA factors are involved in regulating the expression of the gene encoding the cross-linking enzyme transglutaminase (TGase) in hemocyte differentiation (Lin et al, 2008b). The main hemocyte lineages in P. leniusculus, SGCs and GCs, both express a Lz-like transcript (RUNX-family GenBank: CAD44570.1) required for proPO-expressing cells, such as Drosophila CCs and crayfish SGCs and GCs (Lebestky et al, 2000;Söderhäll et al, 2003b).…”
Section: Proteins In P Leniusculus Hematopoiesis -A Comparison With mentioning
confidence: 99%
“…When crude Ast1 from plasma is added to cultured cells, proliferation and cell spreading (migration) are stimulated (5,10). When the ROS level was decreased by incubating the cells for 30 min with 10 M NAC, the APC and reHPT cells did not show any signs of spreading (spindle-shaped morphology) at 48 h compared with control cells and H 2 O 2 -treated cells (Fig.…”
Section: Ros Signaling Is Involved In New Hemocytementioning
confidence: 99%
“…This connective tissue serves as a structural support for the cells inside the tissue and provides a specific microenvironment for the regulation of the differentiating cells. Previously, we demonstrated the importance of extracellular transglutaminase (TGase) activity to control hematopoiesis through the interaction of hematopoietic cells and the extracellular matrix (ECM) to maintain the immature HPT cells inside the hematopoietic tissue (10). The importance of ECM proteins for hematopoiesis has been shown in Drosophila, where a Perlecan homolog, the heparin sulfate proteoglycan Terribly Reduced Optic (Trol), was identified as part of the ECM in the lymph gland (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation